2012
DOI: 10.1037/a0027033
|View full text |Cite
|
Sign up to set email alerts
|

“Robovie, you'll have to go into the closet now”: Children's social and moral relationships with a humanoid robot.

Abstract: Children will increasingly come of age with personified robots and potentially form social and even moral relationships with them. What will such relationships look like? To address this question, 90 children (9-, 12-, and 15-year-olds) initially interacted with a humanoid robot, Robovie, in 15-min sessions. Each session ended when an experimenter interrupted Robovie's turn at a game and, against Robovie's stated objections, put Robovie into a closet. Each child was then engaged in a 50-min structural-developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(220 citation statements)
references
References 48 publications
14
203
0
3
Order By: Relevance
“…One teacher observed that, "as with many stuffed animals, the children seemed to have an attachment to the robot." In prior work, researchers have found that children are indeed attached to the robots-e.g., they are call robots their friends and they are willing to share secrets to robots [2], [18]. Another teacher observed,"they loved the little postcards [that we gave them at the end of the study] and they felt special, and I think that they're so attracted to the robot and sort of curious so that's why what held them, if it weren't something they were scared of.…”
Section: Interviews: Children's Interactions With the Robotmentioning
confidence: 99%
“…One teacher observed that, "as with many stuffed animals, the children seemed to have an attachment to the robot." In prior work, researchers have found that children are indeed attached to the robots-e.g., they are call robots their friends and they are willing to share secrets to robots [2], [18]. Another teacher observed,"they loved the little postcards [that we gave them at the end of the study] and they felt special, and I think that they're so attracted to the robot and sort of curious so that's why what held them, if it weren't something they were scared of.…”
Section: Interviews: Children's Interactions With the Robotmentioning
confidence: 99%
“…To address this, we use an alternative method of open-ended interviews, which have previously explored children's beliefs about robotic agents with promising results [15]. In contrast to prior work in which researchers may guide children to the towards the topic of animacy, We offer children the opportunity to ask self-generated questions towards the robot after HRI scenarios.…”
Section: Measuring Animacy Beliefsmentioning
confidence: 99%
“…Prior work suggests that robots are not so simply categorized by children. Children may think of robots as in-between living and non-living [6], [7], attributing psychological and perceptual abilities but not biological properties to them [8]. The understanding children may have of robots as "sort of this and sort of that"-with some combination properties held by pets, puppets, computers, and people-may make sense to them in a way that may not make sense to adults who follow a stricter categorization scheme.…”
Section: Research Questionsmentioning
confidence: 99%
“…Younger children will care less about the teleoperator and treat the robot as a social other in both conditions [6], [7]. Older children may feel more awkward and less engagement in the Before condition, and thus perform fewer "social" behaviors (e.g., laughter, asking questions, leaning toward the robot vs. away) and learn less in the learning task due to lack of trust [10].…”
Section: B Hypothesesmentioning
confidence: 99%